Research on Threshold Adjustment Algorithm in Adaptive Modulation and Coding - Fan Chen; Chen Meiya; Su Lijun; Zhang Xin; Yang Dacheng (2006 IEEE 17th International Symposium on Personal, Indoor and Mobile Radio Communications, 2006)
Adaptive modulation and coding (AMC) has gained a lot of attention in the research of high speed downlink packet access (HSDPA). The idea is to adapt the transmission to the fast changing channel conditions by the use of different modulation and coding schemes (MCS). In this paper, an adaptive algorithm (ITA) is presented for the AMC technique in HSDPA and a theoretical analysis model is introduced to investigate the throughput and FER of ITA. Subject to the given FER target, the numerical and link level simulation results both show that ITA outperforms the adaptive algorithms